PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH ANORGANIK DI RW 15 KELURAHAN KULIM KECAMATAN TENAYAN RAYA PEKANBARU - Haryani, Heni; ", Suyanto; Azrin, Miftah (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTThe increase in population led to the accumulation of garbage is increasing. Inorganic waste is a major problem that the longer amount is not reduced and often received less attention. The problem is the difficulty of inorganic waste management because it is difficult to rot and decompose. A good waste management requires the participation of the community. The Public Health Department of Medical Faculty of Riau University has made a program that involves the community in managing the inorganic waste to the sorting stage. The program is establishing waste bank assisted. This type of research is descriptive qualitative approach, with in-depth interviews, focus groups, and observation. By using the snowballing sampling technique obtained 26 samples from the population, which acts as a cadre of society, people who do not act as a cadre, community leaders, and lecturers form Public Health Department. The results obtained are the savings into the motivation of people to participate in the management of inorganic waste. The activity was sorting of waste in the household, then people dropping off and weigh to the bank, further cooperation with Labuai waste bank for picking-up and selling the waste, then the Labuaiwaste bank managing inorganic waste into handicrafts in cooperation with the UPPKS (Prosperous Family Income Improvement Effort). Expectations of the people in the management of inorganic waste was increasing public engagement, manufacture passbook, bank development and training of its own garbage crafts.Keywords: Participation, waste management inorganic, waste bank